PENERAPAN MODEL KOOPERATIF TIPE PAIR CHECK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 02 BANDAR SUNGAI KECAMATAN SABAK AUH KABUPATEN SIAK - Andriani, Yulia; N, Lazim; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : This research is motivated by the lack of the students learning outcome in Mathematics. It is indicated by the students’ mean score (68.33). Form 24 students, there are only 10 students (41.67%) who can reach score above the Minimum Mastery Criteria (KKM) and 14 students (58.33%) are still in beneath average score. The score of the minimum mastery criteria (KKM) which is decided is 70. Based on the fact, the researcher tried to use a classroom action research by apply the pair check method. The aim of the research is to increase the learning outcome in Mathematics of students grade IV of SDN 02 Bandar Sungai , Sabak Auh Subdistrict, Siak regency in school year 2015 / 2016. the population is all students of the fourth grade as many as 24 students who consist of 10 male students and 14 female students. The research is conducted as many as three cycles. The cycle I consists of three meetings; two of them are learning processes and the last meeting is final test of the cycle. Cycle II consists of two meetings; one of them is learning process and the last meeting is final test of the cycle. Cycle II consists of three meetings; two of them are learning processes and the last meeting is final test of the cycle. The application of the pair check method can increase the students learning outcome in Mathematics. It is shown by the percentage of the students who reach score above of the Minimum Mastery Criteria (KKM) increase from 41.67% and the mean score is 68.33 to 70.83% and the mean score is 72.08% in the cycle I. It increases again in cycle II become 91.66% and the mean score is 80. There is also an increasing in the percentage of teacher’s activity. It is shown by the percentage of teacher’s activity from 79.15% in cycle I to 97.90% in cycle II. The percentage of students’ activity is also increase from 70.80% in cycle I to 95.80% in cycle II. From the explanation above, it can be concluded that the application of the pair check method can increase the students learning outcome in Mathematics of students of grade IV SDN 02 Bandar Sungai, Sabak Auh subdistrict, Siak regency.Keywords: pair check method, learning outcome in Mathematics